Modeling of Management Processes of Construction Company Business for Increase in its Competitive Stability - Bazanov, Vladimir Evgenievich (Salehan Institute of Higher Education, 2019)
The construction organizations lack adaptive infrastructure. It is required to use more intensively SMART-technologies of design and construction. Purposes of this article: a) the system analysis of categories